DEVELOPMENT OF PROFESSIONAL COMPETENCES OF STUDENTS OF MILITARY EDUCATION ON THE BASIS OF INFORMATION AND COMMUNICATION TECHNOLOGIES (Archive of Conferences, 2021)
Today, the prestige and position of any country on the world stage is measured by its military and economic potential, as well as the level of public awareness of information and communication systems. Therefore, today it is important to systematically transfer knowledge about modern technologies and information communications in all areas, including pre-service military education. In this article, the author discusses in detail the reforms and analysis of the development of professional competencies of students of pre-service military education on the basis of information and communication technologies